SPE/IATMI Asia Pacific Oil &Amp; Gas Conference and Exhibition 2017
DOI: 10.2118/186325-ms
|View full text |Cite
|
Sign up to set email alerts
|

History Match to Support Interpretation of Surfactant Flooding Pilot Test in Tanjung Field

Abstract: Tanjung Field is a brown field which pressure has already depleted and been supported by waterflooding for over a decade. To improve production, surfactant injection, is being studied to be employed in the field. The main objective of this study is to identify parameters that affect oil production increase. History match of the pilot test was carried out to improve the reliability of the reservoir model, hence improving the prediction result of surfactant injection forecast. History match of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Several successful field applications have been recorded in various fields across the world such as Semonga field in Indonesia where injection of surfactants into the carbonate reservoir resulted in 8% reduction in water cut and increased oil recovery [33] and the Daqing oilfield (Chao 522 block) in China with a reported 30% increase in oil recovery from a single well after the injection of 1.0% nonionic surfactant [41]. Furthermore, Aslam et al [4] reported an increase in oil recovery during surfactant flooding using 2.05% anionic surfactant-A127 on Tanjung Field in Indonesia. Despite the success rate of surfactant flooding, the technique has suffered some major setback over the years due to certain factors such as the high cost of surfactant chemicals and its non-biodegradable nature [27].…”
Section: Introductionmentioning
confidence: 99%
“…Several successful field applications have been recorded in various fields across the world such as Semonga field in Indonesia where injection of surfactants into the carbonate reservoir resulted in 8% reduction in water cut and increased oil recovery [33] and the Daqing oilfield (Chao 522 block) in China with a reported 30% increase in oil recovery from a single well after the injection of 1.0% nonionic surfactant [41]. Furthermore, Aslam et al [4] reported an increase in oil recovery during surfactant flooding using 2.05% anionic surfactant-A127 on Tanjung Field in Indonesia. Despite the success rate of surfactant flooding, the technique has suffered some major setback over the years due to certain factors such as the high cost of surfactant chemicals and its non-biodegradable nature [27].…”
Section: Introductionmentioning
confidence: 99%